The poet and the antiquaries : Chaucerian scholarship and the rise of literary history, 1532-1635 - Cook, Megan L. (Megan Leigh), 1981- (University of Pennsylvania Press, 2019)
In The Poet and the Antiquaries, Megan L. Cook explores how early modern historians, lexicographers, religious polemicists, and other readers with extra-literary interests in the English past made Chaucer a figure of lasting cultural significance.